2014
DOI: 10.1002/cne.23447
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cortical input to the primary motor area in the marmoset monkey

Abstract: In primates the primary motor cortex (M1) forms a topographic map of the body, whereby neurons in the medial part of this area control movements involving trunk and hindlimb muscles, those in the intermediate part control movements involving forelimb muscles, and those in the lateral part control movements of facial and other head muscles. This topography is accompanied by changes in cytoarchitectural characteristics, raising the question of whether the anatomical connections also vary between different parts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
82
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(93 citation statements)
references
References 174 publications
(315 reference statements)
11
82
0
Order By: Relevance
“…Thus, some of the false positives identified in the present analysis could possibly be true positives; as a result, the specificity of all tractography techniques would be underestimated. However, studies that used retrograde tracers in the macaque (51) and other primates (52,53) have found that the cortico-cortical and corticothalamic regions identified as being directly connected to the injection sites PCG and V4v tend to be bidirectional. Moreover, our own results suggest that this aspect does not contribute to a large bias in the rate of false positives.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, some of the false positives identified in the present analysis could possibly be true positives; as a result, the specificity of all tractography techniques would be underestimated. However, studies that used retrograde tracers in the macaque (51) and other primates (52,53) have found that the cortico-cortical and corticothalamic regions identified as being directly connected to the injection sites PCG and V4v tend to be bidirectional. Moreover, our own results suggest that this aspect does not contribute to a large bias in the rate of false positives.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, based on mediolateral variations in the size of layer 5 pyramidal neurons, marmoset M1 is composed of 3 architectural divisions (Burman et al, 2008(Burman et al, , 2014a; fields 4a/b and 4c of Paxinos et al, 2012), similar to that of other primates (Watanabe-Sawaguchi et al, 1991).…”
Section: Organization Of Marmoset Motor Areasmentioning
confidence: 96%
“…2, left) originate in medial (6M) and caudal premotor areas (6DC and 6V), whereas areas 6DR and 8C contribute sparser inputs (Burman et al, 2014a); connections of M1 with premotor areas are reciprocal (Burman Table 1). To some extent, variations in the exact composition of inputs to different parts of M1 also reflect its topographic organization, with specific emphases on connections to the regions of head, forelimb and trunk/hindlimb musculature representations (Burman et al, 2014a).…”
Section: Motor Inputsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of premotor input onto M1 560 Premotor areas feature cortical representations of both the upper 561 and lower limb, which are highly interconnected with M1 as well as spi-562 nal motor neurons (Burman et al, 2014;Dum and Strick, 2005;Shimazu 563 et al, 2004). Hence, from an anatomical perspective, premotor areas are 564 likely to be involved in the coordination of movements of the hands and 565 feet alike.…”
mentioning
confidence: 97%